3D Additive Construction: A Potential Solution for the Housing Crisis in the North - Dikel, E. Erhan; Arbuckle, Lauren (The Arctic Institute of North America, 2025)
Northern communities in Canada are facing a severe housing crisis. Living conditions, including the current state of the wood-frame houses, are leading to health complications and other severe problems. Additive construction (AC) is an emerging digital construction technology that could help with this desperate housing situation in the North. AC presents potential advantages that apply to the North, such as significant reduction of labour, construction, and material costs, as well as reduction of construction waste. Fewer skilled workers required to travel from the South and less material required to print houses in a short time will help decrease costs related to construction. As with any new technology, there are potential challenges that should be addressed, such as its economic, social, and environmental impacts; method of transportation; and performance in a cold climate. In addition to that, when designing and printing houses in the North, it is important to consider the social and cultural factors that will influence successful market adoption. Les collectivités nordiques du Canada font face à une grave crise du logement. Les conditions de vie de même que l’état actuel des maisons à ossature en bois posent des problèmes de santé et d’autres difficultés majeures. La construction imprimée en 3D (AC) est une technologie de construction numérique émergente qui pourrait contribuer à améliorer la situation désespérée du logement dans le Nord. La technologie AC offre des perspectives prometteuses pour le Nord, notamment une réduction significative de la main-d’oeuvre requise, des coûts de construction et des déchets de construction. De plus, avec moins de travailleurs qui doivent se déplacer du sud vers le nord et une quantité moindre de matériaux nécessaires pour imprimer rapidement des habitations, cette innovation contribuera également à maîtriser les coûts de la construction. Tout comme pour toute nouvelle technologie, l’impression de maisons soulève des défis, tels que les répercussions économiques, ...